Composite resin composition with excellent dimensional stability

JP7652555B2Active Publication Date: 2025-03-27HYUNDAI MOTOR CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020196349
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-22
Filing Date
2020-11-26
Publication Date
2025-03-27
Estimated Expiration
2040-11-26

Smart Images

  • Figure 0007652555000001
    Figure 0007652555000001
  • Figure 0007652555000002
    Figure 0007652555000002
  • Figure 0007652555000003
    Figure 0007652555000003
Patent Text Reader

Abstract

To provide a composite resin composition that has improved dimensional stability and has physical properties equivalent to or higher than those of long-fiber thermoplastics, and a molded article containing the same.SOLUTION: The composite resin composition includes: semicrystalline polyamide; amorphous polyamide; an acrylonitrile-butadiene-styrene (ABS) resin; a compatibilizer; and a strength-reinforcing agent, with an amount of 30 to 59 wt.% of the semicrystalline polyamide; an amount of 5 to 20 wt.% of the amorphous polyamide; an amount of 5 to 30 wt.% of the ABS resin; an amount of 0.5 to 5 wt.% of the compatibilizer; and an amount of 30 to 50 wt.% of the strength-reinforcing agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite resin composition having excellent dimensional stability and rigidity, and more particularly to a composite resin composition capable of reducing weight, and a molded article produced therefrom. [Background technology]

[0002] In the automotive sector, areas requiring high-strength, high-performance polymer materials are expanding, and in response to this, there is an increasing demand for plastic materials with improved flame retardancy, dimensional stability, impact resistance, weight reduction, tracking resistance, etc. Meanwhile, polyamide, a type of thermoplastic resin, is a type of engineering plastic that has the advantages of high thermal stability and mechanical rigidity and has been used in various industrial fields. However, its range of use has been limited due to its deterioration in physical properties due to hydrolysis in a humid environment and its poor dimensional stability after injection processing.

[0003] In order to improve the dimensional stability of polyamide resins, functional resins have been produced in recent years by applying the long fiber reinforced plastic (LFT) method to polyamide. However, long fiber reinforced plastics have the drawback of increasing process costs because they require an additional process of impregnating the long fibers with plastic after the first extrusion process in which functional additives are added. In addition, materials that use the LFT method have very low fluidity in a molten state, and the repeated process of melting the polymer material at high heat can cause gas to be generated in the final molded product due to material deterioration. In order to overcome such problems in the prior art, there is a demand for the development of a resin composition having improved dimensional stability and performance equal to or better than that of long fiber reinforced plastics, and a molded article thereof. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Korean Patent Publication No. 10-2020-0055223 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made to solve these problems, and an object of the present invention is to provide a composite resin composition containing a semi-crystalline polyamide, an amorphous polyamide, an acrylonitrile-butadiene-styrene (ABS) resin, a compatibilizer, and a strength reinforcing agent, which has improved dimensional stability and physical properties equal to or greater than those of long fiber reinforced plastics, and a molded article containing the same. [Means for solving the problem]

[0006] A composite resin composition according to an embodiment of the present invention includes a semi-crystalline polyamide, an amorphous polyamide, an ABS resin, a compatibilizer, and a strength reinforcing agent.

[0007] The composite resin composition preferably contains 30 to 59% by weight of the semicrystalline polyamide, 5 to 20% by weight of the amorphous polyamide, 5 to 30% by weight of the ABS resin, 0.5 to 5% by weight of the compatibilizer, and 30 to 50% by weight of the strength reinforcing agent. The composite resin composition may further include 0.1 to 10% by weight of an additive including one or more selected from the group consisting of a light resistance stabilizer, a heat resistance stabilizer, an antioxidant, a dispersant, a lubricant, a nucleating agent, a release agent, a metal ion stabilizer, a flame retardant, a dye, and a pigment.

[0008] The semicrystalline polyamide preferably has a relative viscosity of 2.0 to 2.7 as measured in a 98% sulfuric acid solvent. The semi-crystalline polyamide may include one or more selected from the group consisting of polyamide 3, polyamide 4, polyamide 6, polyamide 8, polyamide 9, polyamide 11, polyamide 12, polyamide 6,6, polyamide 6,10, polyamide 6,12, and any combination thereof.

[0009] The amorphous polyamide preferably has a relative viscosity of 1.7 to 2.4 as measured in a 98% sulfuric acid solvent. The ABS resin preferably has a melt flow index of 15 to 40 g / min under conditions of 220° C. and a load of 10 kg. The compatibilizer may include a styrene-N-phenylmaleimide copolymer.

[0010] The strength reinforcing agent may include flat glass fibers. The aspect ratio of the cross section of the flat glass fiber is preferably 2 to 4:1.

[0011] The flat glass fiber is SiO 2 , and Al 2 O 3 It may contain one or more selected from the group consisting of: The strength reinforcing agent may further include a coupling agent.

[0012] A molded product according to an embodiment of the present invention is manufactured by including the composite resin composition. The molded article may be an automobile panoramic sunroof frame. Effect of the Invention

[0013] According to the present invention, the composite resin composition of the present invention and a molded article containing the same have not only the same or better rigidity as conventional long fiber reinforced plastics, but also excellent dimensional stability, and therefore can be widely used in the fields of automobile parts, electrical and electronic equipment, and industrial materials, and is particularly used for automobile parts, such as panoramic sunroof frames, which require high rigidity and dimensional stability and a beautiful appearance. In addition, the composite resin composition of the present invention and a molded article containing the same can replace parts that previously used steel, and in this case, the weight reduction effect can be about 30%. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The composite resin composition according to an embodiment of the present invention may include a semi-crystalline polyamide, an amorphous polyamide, an acrylonitrile-butadiene-styrene (ABS) resin, a compatibilizer, and a strength reinforcement agent, and may further include an additive. Preferably, the composite resin composition may include 30-59 wt% of the semi-crystalline polyamide, 5-20 wt% of the amorphous polyamide, 5-30 wt% of the ABS resin, 0.5-5 wt% of the compatibilizer, and 30-50 wt% of the strength reinforcement agent, and may further include 0.1-10 wt% of the additive.

[0015] That is, since the composite resin composition according to an embodiment of the present invention contains the above components in the above amounts, the molded products manufactured from the composite resin composition have not only the same or better rigidity as conventional long fiber reinforced plastics, but also have excellent dimensional stability, and therefore have the advantage of being widely usable in the fields of automotive parts, electrical and electronic equipment, and industrial materials.

[0016] The semicrystalline polyamide according to an embodiment of the present invention is a base resin, and is not particularly limited as long as it is a polyamide having a crystallizable portion and an amorphous portion in the skeleton. The amorphous portions can include randomly entangled chains of amorphous polymeric material, and the crystallizable portions can include regions of crystalline material packed into ordered arrays of polymer chains, where such crystalline regions are embedded in an amorphous polymer matrix.

[0017] The semi-crystalline polyamide according to one embodiment of the present invention is a semi-crystalline linear polymer that can be polymerized from a monomer of ordinary semi-crystalline polyamide resin, i.e., caprolactam, and has a main chain formed by an amide bond of -[CONH]-. The semi-crystalline polyamide according to one embodiment of the present invention is preferably an aliphatic polyamide, such as one or more selected from the group consisting of polyamide 3, polyamide 4, polyamide 6, polyamide 8, polyamide 9, polyamide 11, polyamide 12, polyamide 6,6, polyamide 6,10, polyamide 6,12, and any combination thereof, and more preferably includes polyamide 6, which has a low viscosity and a relative viscosity of 2.4 or less, and has excellent injection moldability and surface properties for large parts.

[0018] The semicrystalline polyamide according to one embodiment of the present invention has a relative viscosity of 2.0 to 2.7 measured in a 98% sulfuric acid solvent. If the relative viscosity of the semicrystalline polyamide is less than 2.0, the mechanical strength of a molded article including a composite resin composition containing the semicrystalline polyamide may be reduced, and if the relative viscosity exceeds 2.7, the alloy properties of the composite resin may be reduced due to the difference in fluidity between the amorphous polyamide and the ABS resin, resulting in a deterioration in the appearance of the molded article.

[0019] The content of the semicrystalline polyamide according to one embodiment of the present invention is 30 to 59 wt% based on 100 wt% of the total composite resin composition. If the content of the semicrystalline polyamide is less than 30 wt%, there is a risk that a moldability problem occurs when manufacturing a molded product from the composite resin composition containing the semicrystalline polyamide, and if the content exceeds 59 wt%, there is a risk that the mechanical properties of the molded product containing the semicrystalline polyamide are reduced and the molded product cannot be used as a structural member. The semicrystalline polyamide according to an embodiment of the present invention is included in the total composite resin composition at the above relative viscosity and content, so that the rigidity and dimensional stability of the molded product containing the semicrystalline polyamide can be maintained, and the excellent quality of the molded product can be maintained by improving the alloy properties due to the low viscosity.

[0020] The amorphous polyamide according to an embodiment of the present invention is not particularly limited as long as it can delay the crystallization rate of the composite resin composition and molded article containing the same, thereby providing an excellent surface appearance of the final molded article. The amorphous polyamide according to one embodiment of the present invention is a typical amorphous polyamide that can be used in the present invention, i.e., has excellent transparency, resistance to gases, e.g. O 2 and CO 2 For example, polyphthalamide is a polymer in which terephthalic acid monomer is replaced with isophthalic acid, and is preferably PA6I, which has amorphous properties and can dramatically improve the surface properties and dimensional stability of injection molded products when mixed with semi-crystalline resins.

[0021] The amorphous polyamide according to one embodiment of the present invention has a relative viscosity of 1.7-2.4 measured in a 98% sulfuric acid solvent, and a glass transition temperature of 100-130° C. If the relative viscosity of the amorphous polyamide is less than 1.7, the mechanical rigidity of a molded article containing the same may be reduced, and if the relative viscosity is 2.4 or more, the alloy properties may be reduced due to the difference in fluidity between the amorphous polyamide according to the present invention and ABS resin, resulting in a deterioration in the appearance of the molded article. In addition, if the glass transition temperature of the amorphous polyamide is less than 100° C., the injection cycle time may be affected, resulting in a decrease in production efficiency, and if it exceeds 130° C., the appearance quality of the injection molded article may be reduced.

[0022] The content of the amorphous polyamide according to an embodiment of the present invention is 5 to 20 wt%, preferably 5 to 15 wt%, based on 100 wt% of the total composite resin composition. If the content of the amorphous polyamide is less than 5 wt%, the effect of improving dimensional stability and appearance is small, and if it exceeds 20 wt%, the cooling speed is slow when injected into a molded product, and the cycle time increases, which may reduce productivity. The amorphous polyamide according to an embodiment of the present invention is included in the total composite resin composition at the above relative viscosity and content, and thus the dimensional stability of the molded product containing the amorphous polyamide can be improved, thereby solving problems such as warpage of the injection molded product. In addition, when the composite resin composition is produced with the semi-crystalline polyamide, the appearance of the molded product can be improved by controlling the crystallization of the semi-crystalline polyamide.

[0023] The acrylonitrile-butadiene-styrene (ABS) resin according to one embodiment of the present invention is a terpolymer polymerized from three monomers, acrylonitrile, butadiene, and styrene, and is preferably poly(acrylonitrile-co-butadiene-co-styrene). The ABS resin according to one embodiment of the present invention has a melt flow index of 15 to 40 g / min, preferably 20 to 35 g / min, under conditions of 220° C. and a load of 10 kg. If the melt flow index of the ABS resin is less than 15 g / min, the appearance characteristics of the injected surface of the resin may be deteriorated, and if it exceeds 40 g / min, the mechanical properties of the material may be deteriorated.

[0024] The content of the ABS resin according to an embodiment of the present invention is 5-30 wt%, preferably 10-30 wt%, based on 100 wt% of the total composite resin composition. If the content of the ABS resin is less than 5 wt%, the effect of dimensional stability is small, and if it exceeds 30 wt%, the mechanical properties and heat resistance may be deteriorated. The compatibilizer according to an embodiment of the present invention is not particularly limited as long as it improves the alloy properties between the semi-crystalline polyamide, the amorphous polyamide, and the ABS resin. That is, the polyamide resin according to an embodiment of the present invention basically has a polar amide bond of -[CONH]- on the main chain, but the ABS resin is a non-polar resin and has low compatibility with each other, so that without a compatibilizer, the rigidity, product appearance, and dimensional stability may be reduced.

[0025] The compatibilizer according to one embodiment of the present invention is a typical compatibilizer that can be used in the present invention, and may include, for example, one or more selected from the group consisting of styrene-N-phenylmaleimide copolymer, maleic acid grafted polystyrene, maleic acid grafted polyethylene, etc., and is not limited to those containing a specific component, but preferably includes a styrene-N-phenylmaleimide copolymer that improves the deterioration of heat resistance of the resin by alloying ABS. The styrene-N-phenylmaleimide copolymer preferably contains a compound represented by Chemical Formula 1. [ka] Here, x is 10% by weight to 30% by weight, y is 50% by weight to 90% by weight, and z is 0.5% by weight to 5% by weight.

[0026] That is, the styrene-N-phenylmaleimide copolymer is prepared by using styrene, which improves the compatibility with ABS resin, and maleic acid, which has excellent compatibility with polyamide resin, as monomers, and therefore can improve the compatibility between polyamide resin and ABS resin. The compatibilizer according to an embodiment of the present invention may be prepared with a content of 50-90% by weight of styrene monomer, 10-30% by weight of imide monomer, and 0.5-5% by weight of maleic acid monomer based on 100% by weight of the total compatibilizer. If the content of styrene monomer is less than 50% by weight, the compatibility with ABS may decrease, resulting in a decrease in the appearance and mechanical properties of the extrusion product. If the content of imide monomer is more than 90% by weight, the content of imide monomer may decrease, resulting in a decrease in heat resistance and viscosity characteristics, resulting in a decrease in alloy characteristics. If the content of imide monomer is less than 10% by weight, the heat resistance may decrease, and if it exceeds 30% by weight, the heat resistance of the compatibilizer may increase too much, resulting in limited processing. In addition, if the content of maleic acid monomer is less than 0.5 wt%, the compatibility with polyamide resin may decrease, resulting in deterioration of mechanical properties. If the content of maleic acid monomer is more than 5 wt%, the viscosity of the material may become too high, resulting in deterioration of the appearance of the extrusion product and generation of gas during extrusion.

[0027] The content of the compatibilizer according to an embodiment of the present invention is 0.5 to 5 wt% based on 100 wt% of the total composite resin composition. If the content of the compatibilizer is less than 0.5 wt%, the compatibility may decrease, resulting in deterioration of the mechanical properties of the material and the appearance of the extruded product, whereas if the content of the compatibilizer is more than 5 wt%, the mechanical properties may decrease due to the excessive content of the compatibilizer, and gas may be generated during extrusion. The strength reinforcing agent according to an embodiment of the present invention is not particularly limited as long as it can improve the dimensional stability of a molded article containing the strength reinforcing agent.

[0028] The strength reinforcement according to one embodiment of the present invention may include at least one selected from the group consisting of typical strength reinforcements that can be used in the present invention, such as glass fiber, carbon fiber, and basalt fiber, and is not limited to those containing a specific component, but preferably includes glass fiber, which has excellent stiffness and is competitive in price. The cross section of the glass fiber may include one or more cross sections selected from the group consisting of a flat and a circular cross section, and is not limited to a specific cross section, but since the circular cross section is prone to warpage in an injection molded product due to the difference in shrinkage rate of the x, y and z axes relative to the injection flow direction, it is preferable to have a flat cross section that can improve warpage. The glass fiber having a flat cross section may have any non-circular cross section, for example, an elliptical cross section, an oblong-circular cross section, a rectangular cross section, a cross section in which a semicircle is connected to two short sides of a rectangle, and a cocoon cross section, and is not limited to a specific flat cross section.

[0029] The aspect ratio (horizontal / vertical) of the cross section of the flat glass fiber is 2 to 4:1, preferably 4:1. The aspect ratio (horizontal / vertical) of the cross section of the flat glass fiber can be measured by analyzing an image obtained by observing the cross section of the flat glass fiber with a scanning electron microscope (SEM) and drawing a rectangle circumscribing the cross section of the flat glass fiber. The aspect ratio can be obtained by calculating horizontal (length of Ra) / vertical (length of Rb) (wherein horizontal and vertical are the horizontal (Ra) and vertical (Rb) lengths of a rectangle drawn to circumscribing the cross section of the flat glass fiber in each observed image). The flat glass fiber may include E glass, T glass, NE glass, C glass, S glass, S2 glass, R glass, etc., and is not limited to those having specific properties. In addition, the flat glass fiber may be SiO 2 , Al 2 O 3 , CaO and B 2 O 3 The composite resin composition may include one or more selected from the group consisting of the above, and is not limited to the composition containing a specific component. However, it is preferable that the composite resin composition contains all of the above four components, and more preferably, it further contains a coupling agent in order to improve the adhesive strength between the composite resin composition containing the above components and increase the rigidity and dispersibility.

[0030] The content of the strength reinforcement agent according to an embodiment of the present invention is 30 to 50 wt% based on 100 wt% of the total composite resin composition. If the content of the strength reinforcement agent is less than 30 wt%, mechanical properties may be deteriorated, and if it exceeds 50 wt%, the appearance of the injection molded product may be deteriorated and the weight of the injection molded product may increase, reducing the effect of weight reduction. That is, by adding the strength reinforcing agent to the composite resin composition and molded article according to one embodiment of the present invention, it is possible to achieve a balance between rigidity, dimensional stability, and specific gravity, and preferably, by adding flat glass fiber, it is possible to further improve the dimensional stability of the molded article containing the same. In addition, the composite resin composition according to an embodiment of the present invention may further include an additive, which may include at least one selected from the group consisting of typical additives that can be used in the present invention, such as a light resistance stabilizer, a heat resistance stabilizer, an antioxidant, a dispersant, a lubricant, a nucleating agent, a release agent, a metal ion stabilizer, a flame retardant, a dye, and a pigment, and is not limited to those containing a specific component.

[0031] The content of the additive according to an embodiment of the present invention is 0.1-10 wt%, preferably 0.1-5 wt%, based on 100 wt% of the total composite resin composition. If the content of the additive is less than 0.1 wt%, the physical properties may be deteriorated due to deterioration caused by external factors during processing and after product molding, or performance such as light resistance may be deteriorated, and if the content of the additive is more than 10 wt%, the amount of low molecular weight substances may increase during processing, resulting in deterioration of mechanical properties and generation of gas during product molding. In other words, the composite resin composition according to an embodiment of the present invention contains the above components in the above amounts, and thus has the advantage that it not only has a rigidity that is equal to or better than that of conventional long fiber reinforced plastics, but also has particularly excellent dimensional stability.

[0032] The molded product according to an embodiment of the present invention may be manufactured by including the composite resin composition, that is, by mixing the composite resin composition by a commonly used blending method, extruding the mixture at a temperature of 200 to 260°C using a twin-screw melt kneading extruder, and then further processing the mixture through various processes such as injection molding, blow molding, extrusion molding, thermoforming, and press molding, and preferably by injection molding. That is, the composite resin composition according to one embodiment of the present invention and the molded products manufactured therefrom can be widely used in the fields of automobile parts, electrical and electronic equipment, and industrial materials, and can be used in large injection molded product parts that require high rigidity, dimensional stability, and beautiful appearance, such as panoramic sunroof frames among automobile parts. In addition, the composite resin composition according to the present invention and the molded products containing the same can also replace existing parts made of steel, and in this case, the weight reduction effect is advantageous in that the weight can be reduced by about 30%.

[0033] The present invention will be described in more detail with reference to the following specific examples. However, the following examples are merely illustrative to aid in understanding the present invention, and the scope of the present invention is not limited thereto. [Examples 1 to 4 and Comparative Examples 1 to 6: Production of Molded Specimens Containing Composite Resin Compositions] The composite resin compositions containing the components and compositions shown in Table 1 below were uniformly mixed in a ribbon mixer, and then extrusion-molded at a temperature of 200 to 260°C using a twin-screw extruder with L / D of 40 and 40 mm to prepare pellets. The pellets were then injection-molded at a temperature of 250 to 270°C to prepare molded specimens containing the composite resin compositions of Examples 1 to 4 and Comparative Examples 1 to 6.

[0034] [Table 1]

[0035] [Measurement method] The physical properties of each specimen prepared were measured by the following methods. Tensile strength and elongation: ASTM D635 Flexural strength: ASTM D790 Impact strength: ASTM D256 Shrinkage rate: ASTM D955, resin flow direction MD, perpendicular to resin flow direction TD Injection warpage height: Measure the height of the most warped part of the flat mold shown below. Appearance of injection: Glossy when observed with the naked eye, no G / F protrusion phenomenon [Experimental Example: Comparison of Dimensional Stability and Physical Properties of Molded Specimens Produced from Composite Resin Compositions] The dimensional stability, physical properties, tensile strength, etc. of Examples 1 to 4, Comparative Examples 1 to 6, and a long fiber reinforced plastic (LFT) material containing 40% by weight of glass fiber in polyamide 6 as a comparative group, which were produced according to an embodiment of the present invention, were measured by the above-mentioned measuring methods, and the results are shown in Table 2 below.

[0036] [Table 2]

[0037] As shown in Table 2, all of the molded products manufactured from the composite resin compositions of Examples 1 to 4 according to the present invention exhibited excellent mechanical rigidity, injection appearance, and dimensional stability, but the molded products manufactured from the composite resin compositions of Comparative Examples 1 to 6 or the LFT material showed low mechanical strength or poor dimensional stability of the molded products and appearance of the injection products. That is, the composite resin composition according to the present invention and the molded products containing the same have not only a rigidity at a comparable level or higher than that of conventional long fiber reinforced plastics, but also a particularly excellent dimensional stability, and therefore can be widely used in the fields of automobile parts, electrical and electronic equipment, and industrial materials, and can be used in large injection molded product parts that require high rigidity, dimensional stability, and beautiful appearance, such as panoramic sunroof frames among automobile parts. In addition, the composite resin composition according to the present invention and the molded products containing the same can replace existing parts made of steel, and in this case, the weight reduction effect can be reduced to about 30%.

Claims

1. A semicrystalline polyamide; An amorphous polyamide; Acrylonitrile-butadiene-styrene (ABS) resin; A compatibilizer; A strength reinforcing agent, 30 to 59% by weight of the semicrystalline polyamide; 5 to 20% by weight of the amorphous polyamide; 5 to 30% by weight of the ABS resin; 0.5 to 5% by weight of the compatibilizer; 30 to 50% by weight of the strength reinforcing agent; The semicrystalline polyamide is at least one selected from the group consisting of polyamide 3, polyamide 4, polyamide 6, polyamide 8, polyamide 9, polyamide 11, polyamide 12, polyamide 6,6, polyamide 6,10, polyamide 6,12, and any combination thereof; The amorphous polyamide is a polyphthalamide having a structure in which a terephthalic acid monomer is replaced with isophthalic acid, The compatibilizer comprises a styrene-N-phenylmaleimide copolymer; The composite resin composition is characterized in that the strength reinforcing agent is flat glass fiber.

2. The composite resin composition according to claim 1, further comprising 0.1 to 10% by weight of an additive including at least one selected from the group consisting of a light resistance stabilizer, a heat resistance stabilizer, an antioxidant, a dispersant, a lubricant, a nucleating agent, a release agent, a metal ion stabilizer, a flame retardant, a dye, and a pigment.

3. 2. The composite resin composition according to claim 1, wherein the semi-crystalline polyamide has a relative viscosity of 2.0 to 2.7 as measured in a 98% sulfuric acid solvent.

4. 2. The composite resin composition according to claim 1, wherein the amorphous polyamide has a relative viscosity of 1.7 to 2.4 as measured in a 98% sulfuric acid solvent.

5. 2. The composite resin composition according to claim 1, wherein the ABS resin has a melt flow index of 15 to 40 g / min under conditions of 220° C. and a load of 10 kg.

6. The styrene-N-phenylmaleimide copolymer comprises a compound represented by the following Chemical Formula 1, wherein x is 10 wt % to 30 wt %, y is 50 wt % to 90 wt %, and z is 0.5 wt % to 5 wt %. 【Chemistry 1】

7. 2. The composite resin composition according to claim 1, wherein the aspect ratio of the cross section of said flat glass fiber is 2:1 to 4:

1.

8. The flat glass fiber is SiO 2 , and Al 2 O 3 The composite resin composition according to claim 1, comprising at least one member selected from the group consisting of:

9. The composite resin composition according to claim 1 , wherein the strength reinforcing agent further comprises a coupling agent.

10. A molded article comprising the composite resin composition according to claim 1.

11. The molded article according to claim 10, wherein when the molded article made of the composite resin composition replaces an existing steel part, the weight reduction effect is a 30% level.

Citation Information

Patent Citations

  • Polyamide resin composition and molded product using the same

    JP2010248406A

  • Resin composition for use in coated molded article

    JP2010285598A

  • A coating composition for carbon fiber reinforced plastic and manufacturing method of carbon fiber reinforced plastic using the same

    KR1020200055223A

  • Polyamide composition for the production of weldable moulded bodies

    WO2019101851A1